A new symmetrical cryptosystem based cellular automata and chaotic map function. (4th July 2022) - Boudali, Asmaa; Said, Naima Hadj; Ali-Pacha, Adda
Abstract: Multimedia data including text, audio, image, and video are increasingly transmitted over networks or stored in digital format. Therefore, secure transmission and storage are required to preserve it. This is why the utilization of cryptography has become imperative to establish new approaches for rising security. The cryptographic systems rely on cellular automata (CA) and chaotic systems, which are fundamental in various cryptographic applications such as key generation and image encryption. Some of them are complex and others have little key space. In this paper, a novel research work based on cellular automata and chaotic logistic mapping is proposed. Overall, the paper aims to propose a new cryptographic system that produces encrypted data with random characteristics. A novel technique is adopted to develop the evolution of configurations in elementary cellular automata (ECA) which makes the obtained result more random. Simulation results demonstrate that the proposed approach has a high level of security and resists various attacks. In addition, it outperforms some existing image encryption algorithms.